Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa pada teama 8 Sub Tema 1 Lingkungan Tempat Tinggalku Kelas IV di SDN 37 Tungka - Ermah Suriani; Dian Firdiani; Irman Syarif (Universitas Muhammadiyah Enrekang, 2021)
Ermah Suriani, 2021. Application of the Problem Based Learning Model to Improve Student Learning Outcomes on Theme 8 Sub Theme 1 My Living Environment Class IV at SDN 37 Tungka. This study aims to improve student learning outcomes using the Problem Based Learning. The type of research used is Classroom Action Research which consists of two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. The subjects in the study were the fourth grade students of SDN 37 Tungka, totaling 19 people. The research data was obtained by using research instruments of learning outcomes tests and observation sheets. In pre-cycle activities only 6 students with a percentage of 31.57% completed, in the first cycle increased to 12 people with a percentage of 63.15% who completed, and in the second cycle stage increased again to 16 people with a percentage of 84.21%. Based on the results of the study, it can be concluded that the use of the Problem Based Learning can improve student learning outcomes on theme 8 sub-theme 1 of the environment where I live.